Literary Projection of Nature and Environment in AbhijÃ±Äna-ÅšÄkuntalam: Reflection of Faith-Based Care for the Environment - Bipin Kumar Jha; Abhishek Tripathi (UNHI PRESS, 2020)
AbhijÃ±Äna ÅšÄkuntalam, as Sanskrit play by the renowned poet KÄlidÄsa offers the utmost importance to nature and the environment. It is the responsibility of all and everyone, irrespective of their social strata; king, sages, their sons and daughter and their disciplesâ€™ given equal responsibility and accountability to care for the environment. The king is advised not to kill the animals roaming inside a guarded territory of the Ä€Å›rama (cottage) of the sages. ÅšakuntalÄ was advised by her father Kaá¹‡va to look after the plants and animals. The reciprocal nature of mutual dependence between Human and Environment vividly delved in AbhijÃ±Äna ÅšÄkuntalam. The Kingâ€™s major responsibility includes preserving environment, one such example; the text eludes King Duá¹£yanta, taming a mad elephant, destroying the plants, while the king introduces himself to the ÅšakuntalÄ the very first time, another example is, the opening statement in AbhijÃ±Äna ÅšÄkuntalam reflects the concern of environment protection, the very importance of the people who care and nurture environment and have describes as: YÄsá¹›á¹£á¹iá¸¥sraá¹£á¹urÄdyÄ vahatividhihutaá¹ƒ yÄhaviryÄ ca hotrÄ«, Ye DvekÄlaá¹ƒ vidhattaá¸¥ Å›rÅ«tiviá¹£aya guá¹‡Ä yÄ sthitÄ vyÄpyaviÅ›vam, YÄm Ähuá¸¥ sarvabÄ«ja-praká¹›tiriti yayÄ prÄá¹‡inaá¸¥ prÄá¹‡avantaá¸¥, Pratyaká¹£Äbhiá¸¥ prapannastanubhiravatuvastÄbhiraá¹£á¹ÄbhirÄ«Å›aá¸¥ [A.S 1.1]. Eight forms has Shiva, Lord of all and king: And these are water, first created thing; And fire, which speeds the sacrifice begun; those who care for nature; and timeâ€™s dividers, moon and sun; The all-embracing ether, path of sound; The earth, wherein all seeds of life are found; And air, the breath of life: may he draws near, Revealed in these, and bless those gathered here (Ryder,1999). The eight elements described in AbhijÃ±Äna ÅšÄkuntalam viz; the five gross elements along with time and space, and the people in general who care for nature are considered to be the constituents of god or Shiva. The environment and nature treated here as one entity represented here as, Lord Shiva, one of the trinities of Hindu god, shows the reflection of faith in relation to the care for the environment